1986
DOI: 10.1007/bf01965522
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ADP to the amplification of primary platelet aggregation by platelet activating factor (PAF): modulatory role of aspirin

Abstract: Platelet Activating Factor (PAF)-induced human platelet aggregation in citrated plasma is accompanied by activation of the cyclo-oxygenase pathway and release of intracellular constituents including Adenosine-5'-diphosphate (ADP). Inhibition of the cyclo-oxygenase pathway by aspirin prevented the amplification of primary platelet aggregation induced by threshold concentrations of PAF. Removal of ADP by enzymatic systems had little or no effect on PAF-induced full aggregation, but reversed the aggregating effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Apyrase reduced aggregation induced by PLC and PLC + ADP, but did not affect aggregation induced by PLC in combina tion with another stimulus. The combination of aspirin and apyrase did not inhibit aggregation by paired stimuli (PLC + U-46619 and PLC + PAF) but it was reported to inhibit PAF-induced aggregation (23).…”
Section: Discussionmentioning
confidence: 88%
“…Apyrase reduced aggregation induced by PLC and PLC + ADP, but did not affect aggregation induced by PLC in combina tion with another stimulus. The combination of aspirin and apyrase did not inhibit aggregation by paired stimuli (PLC + U-46619 and PLC + PAF) but it was reported to inhibit PAF-induced aggregation (23).…”
Section: Discussionmentioning
confidence: 88%
“…Thus the mechanism of release of alpha granules, as studied here, appears similar to that of dense granules. Indeed, PAF also induces secretion from dense granules in citrated PRP almost completely through the TX pathway [6,9,10,12,13,27]. Working on WP in the presence of Ca 2+, Vargaftig et al [28] found only partial release from dense granules after stimulation with PAF+ EPI.…”
Section: Discussionmentioning
confidence: 97%
“…Release of dense and alpha granules is triggered by the aggregating agents through different mechanisms. The strong agents, like thrombin and calcium ionophores, induce release even after blockade of the TX pathway, while ADP, epinephrine or low doses of collagen do not induce release when this pathway is not viable [5,13]. At variance with a recent paper [30] our data fully support the view [6] that PAF, although active at very low concentrations, should be considered a weak releasing agent, since the release reaction can only be induced when the thromboxane-endoperoxide receptor is stimulated, q-his is apparent in citrated PRP, where BTG release was inhibited by either cyclooxygenase or receptor blockade, and is also supported by the data on WP in the presence of calcium, where PAF did not induce TXB2 synthesis and BTG release was low.…”
Section: Discussionmentioning
confidence: 99%